Quality improvement collaborative: A novel approach to improve infection prevention and control. Perceptions of lead infection prevention nurses who participated. Issue 2 (March 2018) - Adams, Debra; Hine, Victoria; Bucior, Helen; Foster, Wendy; Mukombe, Nyarayi; Ryan, Jane; Smirthwaite, Sandra; Winfield, Jodie
Background: In response to the ongoing infection prevention (IP) challenges in England, a 90-day quality improvement (QI) collaborative programme was developed. The paper discusses the approach, benefits, challenges and evaluation of the programme. Objective: The objective of the collaborative was to develop new approaches to enable sustainable and effective IP. Methodology: Six trusts in the region participated in the collaborative. Each defined their bespoke IP focus. There was no expectation that statistically significant measurable improvements would be identified during the short time frame. The experiences of the participants were sought both during the programme to facilitate its constant review and at the end of the programme to evaluate its effectiveness. The feedback focused on achievements, barriers to change and benefits of participating in a QI collaborative. To measure the potential success of the projects, participants completed the Model for Understanding Success in Quality framework. (MUSIQ; Kaplan et al., 2012). Results: Since each trusts IP focus was bespoke commonalities of success were not evaluated. Participants identified a positive outcome from their QI interventions. The MUSIQ score identified the projects had the potential for success. Discussion: The feedback from the participants demonstrated that it is worthy of further development.